The Study of Stress Among Head Nurses in Selected Hospitals of Tehran - Hosein Mahmoudi; Masood Siratinir; Abbas Ebadi; Sayed Davood Tadrisi; Ali Taiby (Iran University of Medical Sciences, 2009)
Background and Aim: Social changes, economic conditions, social class and living place situations have been understood as stressors for head nurses. Head nurses have an important role in quality of service delivery to clients. The purpose of this study was to examine stress among head nurses in selected hospitals of Tehran.   Martial and Method: This was a descriptive cross-sectional study on 90 head nurses selected by census sampling. The participants filled out a questionnaire containing demographic characteristics and stressors variables. Data were analyzed by SPSS and descriptive and inferential statistical were reported.   Results: The finding showed that 74.4% of head nurses had normal stress and 25.6% of them had severe stress. There was statistically significant relationship between stress and experiencing general management course (P= 0.03).   Conclusion: Role conflict and the absence of organizational support were respectively found to have the most and the least influential effect on stress. Also, job stress in head nurses who had passed general management course was less than the others.